Determinants of Capital Structure: Empirical Evidence from UK Listed Firm Panel Data - Wang, Yichun (2018)
This paper contributes to the capital structure decisions by exploring the determinants of capital structure of UK listed firms. A panel data set of 246 companies listed on FTSE350 from the period of 2008-2017 was analysed. The objectives of the study are to investigate the influence of explanatory variables on financial leverage includes six firm-specific variables and one macro aspect variable such as tangibility, non-debt tax shield, profitability, firm size, growth opportunity, liquidity and GDP growth rate and the appropriate theories to explain the financing decision. Long-term leverage, short-term leverage and total leverage served as the dependent variables and were all calculated using their book value. All seven determinants were examined by the Fixed Effect regression model. This study supports the profitability, firm size, growth opportunity, liquidity and GDP growth rate are negatively related to leverage, while tangibility and non-debt tax shield are positively correlated. The pecking order theory and agency cost theory can be employed to explain the results of four determinants respectively, however, trade-off theory only supports two determinants. Thus, this study is more inclined towards the pecking order theory and agency cost theory.